Time is running out - Antin, Mauritz; Louhio, Eeva; Maija Puutio, Eeva (Information Centre of the World Peace Council, 1982)
Black and white photograph of window in rainy weather; calendar of the year 1982 for the months October, November and December on the bottom. Includes informative text on NATO and the US Pershing II and Cruise Missiles PO-0441